NF-κB signaling in tanycytes mediates inflammation-induced anorexia - Mareike Böttcher; Helge Müller-Fielitz; Sivaraj M. Sundaram; Sarah Gallet; Vanessa Neve; Kiseko Shionoya; Adriano Zager; Ning Quan; Xiaoyu Liu; Ruth Schmidt-Ullrich; Ronny Haenold; Jan Wenzel; et al. (Elsevier, 2020)
Objectives: Infections, cancer, and systemic inflammation elicit anorexia. Despite the medical significance of this phenomenon, the question of how peripheral inflammatory mediators affect the central regulation of food intake is incompletely understood. Therefore, we have investigated the sickness behavior induced by the prototypical inflammatory mediator IL-1β. Methods: IL-1β was injected intravenously. To interfere with IL-1β signaling, we deleted the essential modulator of NF-κB signaling (Nemo) in astrocytes and tanycytes. Results: Systemic IL-1β increased the activity of the transcription factor NF-κB in tanycytes of the mediobasal hypothalamus (MBH). By activating NF-κB signaling, IL-1β induced the expression of cyclooxygenase-2 (Cox-2) and stimulated the release of the anorexigenic prostaglandin E2 (PGE2) from tanycytes. When we deleted Nemo in astrocytes and tanycytes, the IL-1β-induced anorexia was alleviated whereas the fever response and lethargy response were unchanged. Similar results were obtained after the selective deletion of Nemo exclusively in tanycytes. Conclusions: Tanycytes form the brain barrier that mediates the anorexic effect of systemic inflammation in the hypothalamus.